2007
DOI: 10.1016/j.visres.2007.01.022
|View full text |Cite
|
Sign up to set email alerts
|

The geomagnetic field influences the sensitivity of our eyes

Abstract: Experiments involving the orientation of animals, especially birds, have shown that the visual system and geomagnetic field are linked. On the basis of these findings, we have addressed the question of whether there is an influence of the geomagnetic field on light-sensitivity of the visual system in man. Here we report on measurements of the photopic sensitivity of the human visual system for a 0.5s test-stimulus without magnetic field and with the full local field of 48 microT rotated into the line of view. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Numerous studies with varying degrees of reliability have shown that magnetic fields can affect virtually all living organisms, from bacteria to human beings [Presman, 1970;Blakemore, 1975;Binhi, 2002;Wiltschko and Wiltschko, 2005;Pazur et al, 2007;Schuler, 2007]. Eye sensitivity and blood pressure depend on geomagnetic field variations [Thoss and Bartsch, 2007;Zenchenko et al, 2012]. Related issues have long been reviewed and discussed with data from exposure of patients to strong, static magnetic fields during magnetic resonance imaging (MRI) [Schenck, 2000;Hartwig et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies with varying degrees of reliability have shown that magnetic fields can affect virtually all living organisms, from bacteria to human beings [Presman, 1970;Blakemore, 1975;Binhi, 2002;Wiltschko and Wiltschko, 2005;Pazur et al, 2007;Schuler, 2007]. Eye sensitivity and blood pressure depend on geomagnetic field variations [Thoss and Bartsch, 2007;Zenchenko et al, 2012]. Related issues have long been reviewed and discussed with data from exposure of patients to strong, static magnetic fields during magnetic resonance imaging (MRI) [Schenck, 2000;Hartwig et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…Somewhat surprisingly, while magnetodetection in humans is not widely accepted, there is increasing evidence suggesting that such a sense may exist. In recent studies, it has been demonstrated that weak magnetic fields as the geomagnetic ones can provoke evoked potentials in humans (Carrubba et al 2007) or can influence the visual sensitivity of man (Thoss and Bartsch 2007), supporting the evidence for the radical-pair retinal model in humans. Further experiments on magnetodetection have demonstrated, as the first thing, that cryptochrome is necessary for a light-dependent magnetic sense in Drosophila (Gegear et al 2008) and successively that the human cryptochrome CRY2 has the molecular capability to function as a light-sensitive magnetosensor (Foley et al 2011).…”
Section: Section 2: Molecular Mechanisms At the Basis Of Possible Biomentioning
confidence: 65%
“…The mean values and their range of confidence for each subject were calculated from the five values for the threshold intensity obtained for each test time. This approach is justified because it can be assumed that the discrimination thresholds are normally distributed [12]. The averaging of the individual time courses then gave the mean course of the discrimination threshold for all subjects (Figure 2).…”
Section: Methodsmentioning
confidence: 99%